Pregnancy outcome prediction after embryo transfer based on serum human chorionic gonadotrophin concentrations - Balasičová, Katarína; Kraus, Andrea; Peterová, Lucia; Nykolaichuk, Roksolana; Toporcerová, Silvia (Ceska gynekologie, 2022)
OBJECTIVE: The aim of the study was to evaluate the predictive value of the human chorionic gonadotropin (hCG) concentration on the 14th and 16th post-ovulation day after embryo transfer/cryoembryo transfer as well as the dynamics of its increase with respect to the outcome of pregnancy. MATERIALS AND METHODS: In total, 130 embryo transfers and cryoembryo transfers in women aged 22 to 38 years who experienced a single embryo transfer or single cryoembryo transfer with confirmed pregnancy (hCG level over 15 IU/l on 14th post-ovulation day - D14) were selected. The input parameters (hCG D14, hCG D16, hCG D16-D14, hCG D16/D14 and positivity of at least 2.5-fold increase in hCG D16 compared to hCG D14) were evaluated by regression analysis in relation to the outcome parameters (bio-chemical pregnancy, clinical pregnancy, clinical pregnancy terminated by abortion up to 12 weeks of gestation, clinical pregnancy terminated by childbirth). RESULTS: Single concentrations of hCG D14 and D16, as well as the difference between these concentrations, were a statistically significant indicator of the prediction of bio-chemical pregnancy (P = 0.000215, P = 0.000227 and P = 0.000421). Contrary to expectations, the proportion of hCG D16 and D14 concentrations did not show statistical significance for either parameter, as well as the fulfilment of the condition of at least a 2.5fold increase in hCG D16 compared to D14. None of the studied input parameters was confirmed as a statistically significant marker for the prediction of miscarriage in the whole group of patients. However, in the group of confirmed clinical pregnancies, the serum concentration of hCG D16 (P = 0.0248) and the difference between concentrations D16 and D14 (P = 0.0185) were confirmed as a positive predictor of the progression of pregnancy until delivery. CONCLUSIONS: Single hCG concentrations are a good prognostic factor for predicting the outcome of pregnancy, but the determination of the cut-off limit is limited by inter-laboratory deviation as well as by timing of blood collection for hCG determination on the exact post-ovulatory day. The results of individual studies are therefore difficult to use in clinical practice. The dynamics of hCG concentrations appear to be a more reliable predictor of pregnancy outcome. In our cohort, we confirmed the statistical significance of the difference in hCG concentration between the 16th and 14th post-ovulation day not only for the prediction of bio-chemical pregnancy, but also as a predictor of the progression of clinical pregnancy into childbirth. To determine the optimal values of this difference, it is necessary to evaluate a larger group of patients. Conversely, the statistical significance of the proportion of hCG concentrations between the 16th and 14th post-ovulation day was not confirmed.
Keywords: Young Adult; retrospektivní studie; mladý dospělý; prognóza; Pregnancy; těhotenství; Adult; výsledek těhotenství; dospělí; human chorionic gonadotrophin; in vitro fertilisation; Fertilization in Vitro; fertilizace in vitro; choriogonadotropin; Pregnancy Outcome; lidé; ženské pohlaví; přenos embrya; Humans; childbirth after embryo transfer; Embryo transfer; Prognosis; Embryo Transfer; biochemical pregnancy; ongoing pregnancy; Chorionic Gonadotropin; Retrospective Studies; Female; hCG dynamics; cryoembryo transfer